2018
DOI: 10.7759/cureus.2531
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urinalysis on Medical Decision-making and Length of Stay

Abstract: IntroductionThe emergency department (ED) is under pressure to meet length of stay (LOS) metrics for care in the ED. An aspect that we propose affects LOS is the order for urine sample collection and subsequent urinalysis (UA) as both are time consuming steps. This project’s primary goals are to determine if ordering a UA increases LOS and how often UA contributes to clinical decision-making and/or disposition decisions in the ED. Secondary objectives were to identify factors that contribute to the ordering of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…While diagnostic stewardship interventions generally result in a reduction in the number of urine cultures ordered, their impact on appropriate antimicrobial use or clinician's response to an abnormal urinalysis is not clear [74]. Abnormal urinalysis parameters in patients without urinary symptoms are a powerful stimulus to start antibiotic treatment, thwarting diagnostic and antibiotic stewardship interventions [75,76]. The level of pyuria on urinalysis correlates with increasing use of urine cultures and inappropriate antimicrobial prescribing [74].…”
Section: Unintended Consequences Of Urine Culture Stewardshipmentioning
confidence: 99%
See 1 more Smart Citation
“…While diagnostic stewardship interventions generally result in a reduction in the number of urine cultures ordered, their impact on appropriate antimicrobial use or clinician's response to an abnormal urinalysis is not clear [74]. Abnormal urinalysis parameters in patients without urinary symptoms are a powerful stimulus to start antibiotic treatment, thwarting diagnostic and antibiotic stewardship interventions [75,76]. The level of pyuria on urinalysis correlates with increasing use of urine cultures and inappropriate antimicrobial prescribing [74].…”
Section: Unintended Consequences Of Urine Culture Stewardshipmentioning
confidence: 99%
“…The level of pyuria on urinalysis correlates with increasing use of urine cultures and inappropriate antimicrobial prescribing [74]. Routine urinalysis screening is a surprisingly common practice, used in about 25% of emergency department visits, but does not directly impact decisions of care and delays the final disposition in most patients [75,77]. Similar misuse of urinalysis is associated with reflex urine cultures.…”
Section: Unintended Consequences Of Urine Culture Stewardshipmentioning
confidence: 99%
“…Nurses possibly felt as though they ordered more routine urine tests than physicians due to following the local operational protocols that were mainly developed by physicians [ 17 ]. In addition, the results of a recently performed study showed that urinalyses were more likely to be ordered by mid-level providers (e.g., nurse practitioners or physician assistants) than physicians [ 2 ]. Further, we hypothesized that fewer physicians than nurses agreed that routine urine tests should be reduced because this would obstruct the fast work process and prolong a patient’s length of stay in a crowded ED [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urine tests, such as urinalyses and urine cultures, are frequently ordered in the emergency department (ED) [ 1 , 2 ]. A urinalysis is ordered for a variety of indications, for instance, the diagnosis or cause of urinary tract infections (UTIs), kidney failure, or hyperglycemic crisis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Routine urinalysis screening is a surprisingly common practice, used in˜25% of emergency department visits, but does not directly impact decisions of care and delays the final disposition in most patients. 44,45 Even though routine urinalysis testing (ie, screening) is presumed to help detect urinary tract malignancy, renal disease, and diabetes, these diseases are rare in young asymptomatic persons, making false-positive and incidental findings more likely. An annual urinalysis is not warranted for screening healthy asymptomatic individuals without major risk factors for bladder cancer (eg, persons with heavy exposure to cigarette smoke and other bladder carcinogens).…”
Section: Misuse Of Urinalysismentioning
confidence: 99%